Forever This Summer : Love Like Sky #2 - Youngblood, Leslie C. (New York : Little, Brown and Company, 2021)
When eleven-year-old Georgie and her sister Peaches relocate to Bogalusa, Louisiana, with their mother to help their Great Aunt Vie, Georgie becomes involved in the search for the truth about her new friend Markie's mother.
Ages 8-12.
Keywords: Family life -- Louisiana -- Fiction; African Americans -- Fiction; Friendship -- Fiction; Louisiana -- Fiction